Pension Fund Economics and Finance : Efficiency, Investments and Risk-Taking - Bikker, Jacob (London : Taylor and Francis, 2018)
"Pension fund benefits are crucial for pensioners' welfare and pension fund savings have accumulated to huge amounts, covering a major part of world-wide institutional investments. However, the literature on pension fund economics and finance is rather limited, caused, in part, to limited data availability. This book contributes to this literature and focuses on three important areas. The first is pension fund (in)efficiency, which has a huge impact on final benefits, particularly when annual spoilage accumulates over a lifetime. Scale economies, pension plans complexity and alternative pension saving plans are important issues. The second area is investment behavior and risk-taking. A key question refers to the allocation of investments over high risk/high return and relatively safe assets. Bikker investigates whether pension funds follow the life-cycle hypothesis: more risk and return for pension funds with young participants. Many pension funds are rather limited in size, which may raise the question how financially sophisticated the pension fund decision makers are: rather professionals or closer to unskilled private persons? The third field concerns two regulation issues. How do pension fund respond to shocks such as unexpected investment returns or changes in life expectancy? What are the welfare implications to the beneficiary for different methods of securing pension funding: solvency requirements, a pension guarantee fund, or sponsor support? This groundbreaking book will challenge the way pension fund economics is thought about and practiced."--Provided by publisher.
part, I Efficiencyp -- chapter 1 Introduction / Jacob A. Bikker -- chapter 2 Is there an optimal pension fund size? -- A scale-economy analysis of administrative and investment costs 1 / Jacob A. Bikker -- chapter 3 The impact of scale, complexity and service quality on the administrative costs of pension funds 1 -- A cross-country comparison / Jacob A. Bikker Onno W. Steenbeek Federico Torracchi -- chapter 4 Cost differences between pension funds and life insurers in providing pensions / Jacob A. Bikker -- part, II Investment behaviour and risk-taking -- chapter 5 The eligibility of emerging-market bonds for pension fund portfolios / Zaghum Umar Laura Spierdijk -- chapter 6 Mean reversion in stock prices -- Implications for long-term investors 1 / Laura Spierdijk Jacob A. Bikker -- chapter 7 Pension fund investment policy, risk-taking, ageing and the life-cycle hypothesis 1 / Jacob A. Bikker Dirk W.G.A. Broeders David A. Hollanders Eduard H. M. Ponds -- chapter 8 Investor sophistication and risk-taking 1 / Jan de Dreu Jacob A. Bikker -- chapter 9 Investment risk-taking by institutional investors 1 / Janko Gorter Jacob A. Bikker -- part, III Risk-taking and regulation -- chapter 10 Measuring and explaining implicit risk sharing in defined-benefit pension funds 1 / Jacob A. Bikker Thijs Knaap Ward E. Romp -- chapter 11 Utility-equivalence of pension security mechanisms / D.W.G.A. Broeders An Chen Birgit Schnorrenberg.
Keywords: Pensions; Social security individual investment accounts